Lactobacillus plantarum PCS 26 as a probiotic dietary supplement in Slovenian patients with metabolic syndrome: a pilot clinical study - Mario Gorenjak; Dejan Škorjanc; Pavel Skok (Acta Medico-Biotechnica, 2015)
Purpose: In this study, we aimed to determine the effect of a probiotic dietary supplement on physical-anthropometric and biochemical markers in Slovenian patients with metabolic syndrome.Methods: This prospective, randomized, double-blind, placebo-controlled pilot clinical trial involved 16 volunteers who consumed a probiotic dietary supplement over a period of 3 months. The volunteers underwent clinical assessments before and at the end of the period of consuming the dietary supplement or placebo.Results: At a concentration of 1 × 109 colony-forming units per day (N = 8), the Lactobacillus plantarum PCS 26 supplement decreased waist circumference (p = 0.043), lowered serum cholesterol (p = 0.028), and maintained serum adiponectin levels (p = 0.629). In the group that received the placebo (N = 8), no differences were found in the waist circumference (p = 0.750) or serum cholesterol levels (p = 0.225); however, we found a statistically significant reduction of the serum adiponectin levels (p = 0.036).Conclusion: Although the number of patients examined was too low to draw any firm conclusions, dietary supplementation with the probiotic strain Lactobacillus plantarum PCS 26 exerted some favorable effects that could alleviate the symptoms of metabolic syndrome and reduce the clinical manifestations and risks of cardiovascular diseases. These results represent a starting point to carry out an extensive long-term clinical trial that would provide insight into the mechanisms of action of probiotic bacteria in preventing or relieving metabolic syndrome or its components.